2018
DOI: 10.1108/jfmm-05-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Fashion self-congruity: scale development and validation

Abstract: Purpose The purpose of this paper is to develop and validate measurement properties of a scale measuring fashion self-congruity (FSC). Design/methodology/approach Based on the existing literature of self-congruity, and four studies carried out as a part of this research, the FSC scale has been validated in a step-by-step process following the scale validation methodology suggested by Churchill (1979). Findings The final version of the scale incorporates nine items classified into three dimensions: actual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
0
20
0
2
Order By: Relevance
“…Based on the guidelines proposed by Churchill (1979) and Anand and Kaur (2018), the scale development procedure of this study involves three stages: item generation, scale purification and scale validation. The scale development process is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the guidelines proposed by Churchill (1979) and Anand and Kaur (2018), the scale development procedure of this study involves three stages: item generation, scale purification and scale validation. The scale development process is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The scale was purified using a four-step instrument refinement process suggested by previous studies (Anand and Kaur, 2018; Netemeyer et al , 2003). First, this study examined the correlation between each item of a concept and the total score for that concept (item-to-total correlation 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, fashion consumption is more complex; fashion constructs identity (Anand and Kaur 2017), indicating status, lifestyle, and belonging (Goldsmith and Clark 2008). Fashion sends symbolic signals to others that portrays social self (Anand and Kaur 2017) and Nash (2019) found that acquiring new fashion increased self-confidence. Hudson and Hudson (2003) postulate that marketing activities are positioned from the perspective that consumption increases personal satisfaction that contributes to feelings of wellbeing (O'Guinn and Faber 1989).…”
Section: Background Contextmentioning
confidence: 99%
“…Other consumption contexts appear more advanced, particularly the current nudge to reconsider single-use plastic (Howard et al 2019), and more consumers now carry shopping bags, water bottles, and reusable coffee cups with lids to avoid plastic waste. Yet, fashion consumption is more complex; fashion constructs identity (Anand and Kaur 2017), indicating status, lifestyle, and belonging (Goldsmith and Clark 2008). Fashion sends symbolic signals to others that portrays social self (Anand and Kaur 2017) and Nash (2019) found that acquiring new fashion increased self-confidence.…”
Section: Background Contextmentioning
confidence: 99%